Antimicrobial Activity of Some EndemicVerbascum and Scrophularia Species from Turkey - DULGER, BASARAN; HACIOGLU, NURCIHAN (Asian Journal of Chemistry, 2010)
The methanol extracts obtained from three endemic Verbascum L. species (V. cariense Hub.-Mor., V. adenophorum Boiss. and V. inulifolium Hub.-Mor.) and two endemic Scrophularia L. species (S. depauperata Boiss. and S. mersinensis Lall) have been investigated for their antimicrobial activity. Antimicrobial activity was determined with Escherichia coli ATCC 11230, Staphylococcus aureus ATCC 6538-P, Klebsiella pneumoniae UC57, Pseudomonas aeruginosa ATCC 27583, Proteus vulgaris ATCC 8427, Bacillus cereus ATCC 7064, Mycobacterium smegmatis CCM 2067, Listeria monocytogenes ATCC 15313, Micrococcus luteus CCM 169, Candida albicans ATCC 10231, Rhodotorula rubra DSM 70403, Kluyveromyces fragilis ATCC 8608, Debaryomyces hansenii DSM 70238 and Hanseniaspora guilliermondii DSM 3432 by the disk diffusion method. The extracts of all plant species had strong antimicrobial activity against the Gram-positive bacteria and yeasts, but no activity was observed against the Gram-negative bacteria used in this study.